Analisis Pengetahuan Etnomatematika Guru Sekolah Dasar Di Kecamatan Muara Tembesi - Fitria Febriani (Jurnal Inovasi Pendidikan Dasar, 2020)
The research aimed to analyzed integration of regional culture on mathematics learning in elementary schools in Muara Tembesi District. The focus of this study's problem is the teacher's knowledge about ethnomatematics at the elementary school level. This research uses a mixed method approach, which is a quantitative approach and a qualitative approach. The research sample was 18 elementary school teachers from a total population of 249 state elementary school class teachers in Muara Tembesi District. The results of this study indicated that class teachers did not know ethnomatic. There was 22% of teachers had a high ethnomatematics knowledge, 33% of teachers had medium ethnomatematics knowledge, 45% teachers had low ethnomatatics knowledge. This result of the research can be used as reference material to overcome existing obstacles, for example in making modules, teaching materials and learning.   Keywords: Ethnomathematics, Local wisdom, Primary school